Elastic Stress-Strain Behaviour of Concrete with Potential Pineapple Leaf Fibre-Reinforced - Hadipramana, Josef; Fetra Venny Riza; Zulkifli Siregar; Shahrul Niza Mokhatar (International Journal of Integrated Engineering, 2024)
In the stress-strain curve, the stress in the linear region of concrete increases when reinforced with fibre reinforcement. This research aims to investigate the potential of natural fibre from pineapple leaves as reinforcement in concrete regarding its elastic modulus. The natural fibre of pineapple leaves has good tensile strength and is not inferior to the artificial fibre commonly used in fibrous concrete. This research used a pineapple leaf fibre (PLF) composition of 0.04%, 0.09% and 0.15% wt of cement with a water-cement ratio of 0.38. The compressive strength applied is only limited to 40% of the design concrete strength to see the stress-strain character in the elastic region of the pineapple leaf fibrous concrete. The research results show that the amount of pineapple fibre 0.15% provides higher strength and 0.04% and 0.09% fibre in line with ACI and Eurocode. During the hardening process, concrete contains pineapple leaf fibre. The stress is higher than normal concrete for 7 days. Normal concrete begins to approach the stress of fibre concrete when it is 28 days old. Pineapple leaf fibre in concrete contributes to strength even when the concrete is at an early age.